A Programmable Liquid Crystal Elastomer Metamaterials With Soft Elasticity - Liang, Xudong; Li, Dongfeng (Frontiers in Robotics and AI, 2022)
Liquid crystal elastomers (LCEs) are a rubbery network of polymers with ordered liquid crystal mesogens. The combination of rubber elasticity and the anisotropic liquid crystalline order gives exceptional mechanical properties, like soft elasticity, where near-constant stress accompanies large elastic deformation in the material. However, the soft elasticity in LCEs is often bounded by the intrinsic molecular interactions and structures, limiting the range of programmable mechanical properties and functionalities. Here, we demonstrate that the semi-soft elasticity of LCEs can be integrated into the framework of metamaterials to realize markedly programmabilities. Under uniaxial deformation, each state of the building blocks in metamaterials and the molecular composition of the nematic LCEs is associated with a distinctly different stress-strain relation that is fully elastic. Taking advantage of the tunable bending and stretching deformation enabled by the geometry of the building blocks and the semi-soft elasticity of the nematic LCE in the metamaterials, we can engineer the local stretch and stress at an unmet level of their counterpart composed by elastomers. Numerical simulations and analytical models are developed to relate the metamaterial geometries and the LCE soft elasticity to the mechanical responses. In addition, an elastic region with near-zero stiffness up to a stretch of 1.4 can be designed by connecting the compliant responses due to bending deformation and the soft elasticity in the LCE. We expect that the specialized mechanical tunability enabled by the LCE metamaterials can facilitate the development of advanced forms of mechanical metamaterials and impact the design of robotic systems.